2012
DOI: 10.1111/j.1525-1470.2012.01866.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐Analysis of Randomized, Controlled Trials Comparing Particular Doses of Griseofulvin and Terbinafine for the Treatment of Tinea Capitis

Abstract: Two oral antifungal agents, griseofulvin and terbinafine, have regulatory approval in the United States, but it is unknown whether one has superior overall efficacy. Genus-specific differences in efficacy are believed to exist for the two agents. It is not clear at what doses and durations of treatment these differences apply. The goals of this meta-analysis were to determine whether a statistically significant difference in efficacy exists between these agents at a given dose and duration of each in tinea cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
1
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 17 publications
(46 reference statements)
3
56
1
6
Order By: Relevance
“…[7] A carrier in the household, usually a child, can also be a source of reinfection. Trichophyton species are more responsive to terbinafine than griseofulvin as seen in certain studies, [8,9] and the same was observed in our patient.…”
supporting
confidence: 89%
“…[7] A carrier in the household, usually a child, can also be a source of reinfection. Trichophyton species are more responsive to terbinafine than griseofulvin as seen in certain studies, [8,9] and the same was observed in our patient.…”
supporting
confidence: 89%
“…Multiple meta-analyses have demonstrated a similar efficacy for a 6-week course of griseofulvin and a 4-week course of terbinafine [17, 36, 39]. However, a difference in efficacy was found based on the infectious organism.…”
Section: Terbinafinementioning
confidence: 99%
“…However, a difference in efficacy was found based on the infectious organism. Terbinafine demonstrated superiority in treating T. tonsurans and a similar efficacy in treating T. violaceum , while griseofulvin was superior in treating M. canis and other Microsporum species [36, 40]. Lipozencic et al [41] showed that longer courses of terbinafine do not improve its efficacy against Microsporum species, concluding that terbinafine should not be a first line for tinea capitis infections caused by Microsporum species.…”
Section: Terbinafinementioning
confidence: 99%
See 1 more Smart Citation
“…Griseofulvin is the treatment of choice for cases caused by Microsporum species, and it has a long-term safety profile [12]. Nevertheless, as it was not easily available for prescription in our country, we opted to give terbinafine, a broad-spectrum agent that have been shown to be comparable in efficacy and safety with griseofulvin, with good results in our patient and no adverse effects [10,11].…”
Section: Discussionmentioning
confidence: 97%